REFORMULASI KONSEP DIVERSI BERDASARKAN CITA HUKUM NON-DISKRIMINASI - Airlangga, Rendy; Pradipta, Hizkia Andhian; Erdianto, Dyta Widi (Refleksi Hukum: Jurnal Ilmu Hukum, 2023)
The SPPA Law carries restorative justice approach in the form of diversion. The application of restorative approach in SPPA Law has the aim of protecting the child. However, the implementation adheres to discriminatory requirements. The formulation of the problems are: (1) What are the ideal conditions for diversion? (2) What are the problems in the diversion agreement? The method that being used in this study is normative juridical method with statutory and conceptual approach. The application of diversion should be executed for all ABH. Diversion requirements limit the application of restorative justice and provide space to take revenge on ABH. The diversion agreement can create a sense of injustice in society. Reconciliation and return to parents are not an effective way of diversion. Participation in education and community service should be the key so that ABH do not repeat their actions.